The Prognostic Value of the Age-Adjusted Charlson Comorbidity Index Among the Elderly with Breast Cancer - Wang Z; Zhong Y; Zhou Y; Mao F; Zhang X; Wang C; Sun Q (Clinical Interventions in Aging, 2023)
Zhe Wang, Ying Zhong, Yidong Zhou, Feng Mao, Xiaohui Zhang, Changjun Wang, Qiang Sun Department of Breast Surgery, Peking Union Medical College Hospital, Peking Union Medical College, Chinese Academy of Medical Sciences, Beijing, 100730, People’s Republic of ChinaCorrespondence: Qiang Sun, Email sunqpumch@163.comPurpose: This study aimed to assess the effect of comorbidities on prognosis using the Age-adjusted Charlson Comorbidity Index (ACCI) among the elderly with breast cancer (BC).Methods: This study included 745 patients divided into two groups following the ACCI score (≤ 3 vs > 3). Multivariate logistic regression analysis was conducted for all kinds of outcomes, including BC-specific death (BCSD) and non-breast cancer-specific death (NBCSD). The Kaplan–Meier curves were plotted, and survival analysis was conducted for disease-free survival (DFS), overall survival (OS), BC-specific survival (BCSS), and non-BCSS (NBCSS).Results: A significantly higher NBCSD was found in the high-score (ACCI > 3) group than in the low-score (ACCI < 3) group (p = 0.032). The multivariate logistic regression analysis revealed ACCI score as an independent affecting factor for all-cause death (hazard ratio [HR] = 0.42, 95% confidence interval [CI]: 0.22– 0.83, p = 0.012) and NBCSD (HR = 0.41, 95% CI: 0.20– 0.87, p = 0.020). The Kaplan–Meier curves revealed statistical differences only in NBCSS between the two groups (p = 0.039). Subgroup analysis revealed a worse prognosis in the high-score group for OS and NBCSS among hormone receptor-positive participants and those who without undergoing axillary dissection or receiving chemotherapy (all p < 0.05). Multivariate Cox regression analysis revealed ACCI as an independent prognostic predictor for OS (HR = 2.18, 95% CI: 1.22– 3.92, p = 0.009) and NBCSS (HR = 2.04, 95% CI: 1.02– 4.08, p = 0.044).Conclusion: ACCI was indeed an effective indicator of the effects of comorbidities on survival among elderly patients with BC. However, the co-effect from age and comorbidities was not significant enough on cancer-specific prognosis, although it exerted a significant effect on treatments received.Keywords: comorbidity, elderly, breast cancer, Age-adjusted Charlson Comorbidity Index, prognosis